2014
DOI: 10.1212/wnl.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Optimal target localization for subthalamic stimulation in patients with Parkinson disease

Abstract: Objective:To further determine the causes of variable outcome from deep brain stimulation of the subthalamic nucleus (DBS-STN) in patients with Parkinson disease (PD).Methods:Data were obtained from our cohort of 309 patients with PD who underwent DBS-STN between 1996 and 2009. We examined the relationship between the 1-year motor, cognitive, and psychiatric outcomes and (1) preoperative PD clinical features, (2) MRI measures, (3) surgical procedure, and (4) locations of therapeutic contacts.Results:Pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
129
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 41 publications
5
129
2
Order By: Relevance
“…Gender distribution of patients, disease duration, UPDRS 3 scores (on and off medication), Hoehn and Yahr staging, L-dopa equivalent dosages and dopamine agonist use are in agreement with the already described patients undergoing bilateral STN DBS 10 25. All baseline patient characteristics were similar except for the ‘previous history of personality disorders’, but when focusing on IN versus OUT groups, this last and only difference disappears, illustrating the impact of the limited number of patients in the subgroup IN-OUT and BORDER.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Gender distribution of patients, disease duration, UPDRS 3 scores (on and off medication), Hoehn and Yahr staging, L-dopa equivalent dosages and dopamine agonist use are in agreement with the already described patients undergoing bilateral STN DBS 10 25. All baseline patient characteristics were similar except for the ‘previous history of personality disorders’, but when focusing on IN versus OUT groups, this last and only difference disappears, illustrating the impact of the limited number of patients in the subgroup IN-OUT and BORDER.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental and clinical evidence has already pointed to an involvement of the ZI in PD physiopathology and an STN DBS-like effect when the current spreads to or directly stimulates the ZI 9–11. Welter et al 10 already showed a best motor outcome when stimulating contacts within the STN compared with the ZI. The degree of motor improvement postoperatively indicates a sustained beneficial effect on patients despite the leads group while maintaining an important reduction of medication including daily L-dopa (around 40% and 30%, respectively, for the IN and OUT groups).…”
Section: Discussionmentioning
confidence: 95%
“…Most studies were performed retrospectively and in a small number of patients. In addition, inconsistencies in the efficacy and adverse effects of ZI stimulation exist and likely reflect the inability to directly target the ZI resulting in variability of contact placement [20-23, 31, 32]. Methods for visualization of the rZI allowing direct stereotactic targeting have recently been reported [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 1 study found a level of improvement of 64%. 37 Not only did the authors acknowledge that their inclusion criteria may have been more restrictive than those of previous studies, but they also performed surgery after local anesthesia was administered to the patients, and clinical tests were performed during the surgery. Moreover, they did not reveal their stimulation parameters, whereas we were able to demonstrate a significant reduction of TEED when using 3D-SPACE-FLAIR imaging, which may enable slower battery consumption.…”
Section: Discussionmentioning
confidence: 99%